2019
DOI: 10.1097/01.aoa.0000557689.29580.5f
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Remifentanil Patient-controlled Analgesia Versus Intramuscular Pethidine for Pain Relief in Labour (RESPITE): An Open-label, Multicenter, Randomized Controlled Trial

Abstract: Objective Approximately a third of women receiving pethidine during labour subsequently require an epidural, which provides effective pain relief but increases the risk of instrumental delivery. Remifentanil patient-controlled analgesia (PCA) is a potent synthetic opioid with an ultra-short half-life, making it a potential alternative to pethidine. The RESPITE trial aimed to determine epidural rates among women using remifentanil PCA compared to pethidine. Design Randomised, parallel, open-label trial in 14 UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Despite underreporting of serious adverse events was likely, the conclusion was that the risk of potentially lifethreatening adverse events seems to be low 31 When Remifentanil PCIA was compared to pethidine, maternal desaturation was 3 times more frequent with Remifentanil in the RESPITE trial. 12 This result is in line with the results of another randomized trial demonstrating a significantly higher incidence of maternal desaturation with Remifentanil than with fentanyl and meperidine 10 Conclusion Maternal respiratory depression is more common with Remifentanil than with other opioids or epidural analgesia.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Despite underreporting of serious adverse events was likely, the conclusion was that the risk of potentially lifethreatening adverse events seems to be low 31 When Remifentanil PCIA was compared to pethidine, maternal desaturation was 3 times more frequent with Remifentanil in the RESPITE trial. 12 This result is in line with the results of another randomized trial demonstrating a significantly higher incidence of maternal desaturation with Remifentanil than with fentanyl and meperidine 10 Conclusion Maternal respiratory depression is more common with Remifentanil than with other opioids or epidural analgesia.…”
Section: Discussionsupporting
confidence: 76%
“…However, Apgar scores, incidence of fetal acidosis, need for neonatal resuscitation and NICU admission were similar. 12 Remifentanil vs Fentanyl In a 2010 prospective, randomized, double-blind study comparing PCIA with Remifentanil meperidine or fentanyl, no difference was found in Apgar scores, cord pH and BE, NACS and CTG reactivity. 10 In a 2012 retrospective cohort study comparing Remifentanil vs Fentanyl PCIA, Fentanyl was found to be associated with a higher need for neonatal resuscitation 13…”
Section: Neonatal Safety Remifentanil Vs Neuraxial Analgesiamentioning
confidence: 99%
See 1 more Smart Citation